The LSPE-Strip feed horn array. (24th January 2022) - Franceschet, C.; Del Torto, F.; Villa, F.; Realini, S.; Bongiolatti, R.; Peverini, O.A.; Pezzotta, F.; Viganó, D.M.; Addamo, G.; Bersanelli, M.; Cavaliere, F.; Cuttaia, F.; et al.
Abstract: In this paper we discuss the design, manufacturing and characterization of the feed horn array of the Strip instrument of the Large Scale Polarization Explorer (LSPE) experiment. Strip is a microwave telescope, operating in the Q- and W-band, for the observation of the polarized emissions from the sky in a large fraction (about 37%) of the Northern hemisphere with sub-degree angular resolution. The Strip focal plane is populated by forty-nine Q-band and six W-band corrugated horns, each feeding a cryogenically cooled polarimeter for the detection of the Stokes Q and U components of the polarized signal from the sky. The Q-band channel is designed to accurately monitor Galactic polarized synchrotron emission, while the combination of Q- and W-band will allow the study of atmospheric effects at the observation site, the Observatorio del Teide, in Tenerife. In this paper we focus on the development of the Strip corrugated feed horns, including design requirements, engineering and manufacturing, as well as detailed characterization and performance verification.